Peer Groups and Drugs as Factors of Drug Abuse (Case Study of Drug Abusers Deciding to be Drug Users in the Context of Interpersonal Communication in Jakarta) - Khuluqo, Ihsana El; Rahman, Nurlina (International Journal of Psychosocial Rehabilitation, 2020)
–This study aims to reveal the factors that trigger drug abusers to decide using NAZA (Narcotics, Alcohol, Additives) by understanding the peer groups or reference groups of NAZA itself. Phenomenological qualitative research methods are conducted to achieve these objectives. There were 16 informants, most of whom ranging in the age of 10 to 16 when they started using NAZA. Determination of informants is done using the snow-ball sampling method. The results of this study indicate that someone who possesses a tendency of drug abuse in the end decided to use NAZA by looking at the dominant factors, i.e peer groups and NAZA availability. It is expected that this research can give a deeper understanding to the society, especially families and academic institutions in order to trace the early symptoms of drug abusers, which has become a very worrisome social phenomenon nowadays.